Record of an unknown species of Aylacostoma (Gastropoda: Hemisinidae) evidenced by molecular data (Acta Scientiarum. Biological Sciences, 2025)
Gastropods belonging to the Hemisinidae family are distributed in the Neotropical region, mainly in Central and South America, with Aylacostoma being a native genus of South America, as documented in the Paraná River Basin. The Ivaí River is one of the last rivers in the state of Paraná free of dams along its main channel. The future construction of hydroelectric dams could lead to the extinction of populations, including those of Aylacostoma, as occurred with the construction of the Yacyretá reservoir (in the Argentina–Paraguay region). The morphological similarity between species of the genus and the limited number of specialized taxonomists may result in an underestimation of the diversity of these organisms in the region. Molecular techniques have become an invaluable tool for the characterization of gastropod populations. The main objective of this study was to provide a record of an unknown species of Aylacostoma found in the Ivaí River, as indicated by molecular data. The COI mitochondrial region of five specimens was sequenced and subsequently compared with other Hemisinidae and Thiaridae species available in GenBank. The genetic distances observed for Aylacostoma sp. were 5.4% with A. chloroticum and 6% with A. brunneum, indicating that it is a distinct species from those available in GenBank.